Stress that motivates : self-talk secrets for success - Scott, Dru (Crisp Pub. Menlo ParkUS, 1992)
Defines stress; discusses the link between stress, motivation and self-talk; explains how to chart one's stress-motivation profile; shows how harmful stress could be reduced through the self-coaching process. Examines stress factors including burnout. Other issues dealt with include: procrastination, determining priorities and pressures; and reinforcements.